STUDI PENGARUH PENYETELAN RELE JARAK PADA SALURAN UDARA TEGANGAN TINGGI 150 KV TERHADAP KAWAT PENGHANTAR HVCRC 1x310 mm² dan ACCC 1x310 mm² - Andri Yulias Saputra; Abdul Multi (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2021)
The faults Overhead line is generally caused by short circuit, overload, lightning surge, and tree. Distance relay is one of the protection equipments over the overhead line, and as the main protection by measuring fault impedance magnitude and comparing it to intended impedance. Distance relay setting has wide working area ranging from zone-1, zone-2, and zone-3. The setting must be adjusted when the equipment replacement exists. The replacement of overhead line conductor wire of ACSR 1 x 240 mm² into HVCRC 1 x 310 mm² and ACCC 1 x 310 mm² causing the necessity of re-setting adjustment in purpose of obtaining the appropriate one. This thesis is done by quantitative method which needs parameters in term of number. According to the calculation, the setting is obtained that zone-1 = 41,29257 Ω by t1 = instantaneous, zone-2 = 58,82457 Ω by t2 = 0,8 second, and zone-3 = 69,34377 Ω by t3 = 1,6 second.